2014
DOI: 10.1103/physrevb.90.020506
|View full text |Cite
|
Sign up to set email alerts
|

Realization of a single-Cooper-pair Josephson laser

Abstract: MAIN BODY

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
146
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(149 citation statements)
references
References 39 publications
2
146
0
Order By: Relevance
“…Recent experiments on such systems, using conductors such as Josephson junction (JJ) devices [1][2][3], or quantum dots [4,5], have demonstrated that coherent interactions between a conductor and a cavity can generate large non-equilibrium photon populations. Parallels can be drawn between cavity-conductor hybrids and quantum optical devices such as the micromaser in which a stream of excited atoms flows through an optical cavity [6,7]; in both cases the photons in the cavity act back on the photon generation process leading to strongly nonlinear dynamics and dissipative phase transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments on such systems, using conductors such as Josephson junction (JJ) devices [1][2][3], or quantum dots [4,5], have demonstrated that coherent interactions between a conductor and a cavity can generate large non-equilibrium photon populations. Parallels can be drawn between cavity-conductor hybrids and quantum optical devices such as the micromaser in which a stream of excited atoms flows through an optical cavity [6,7]; in both cases the photons in the cavity act back on the photon generation process leading to strongly nonlinear dynamics and dissipative phase transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Following this discussion, we are confident that the classical, nonlinear dynamics analyzed in this work is indeed accessible in realistic circuits similar to those in reference [29] and opens the door to study the interplay of driving, dissipation and resonances under well controlled conditions.…”
Section: Conclusion and Discussionmentioning
confidence: 87%
“…Such spectra have been recently investigated experimentally in Ref. [29]. Resonances [i.e., stable steady-state solutions of (4) or (8) quencies ω = 1/n, 2/n, 3/n, .…”
Section: Higher Order Resonancesmentioning
confidence: 99%
See 2 more Smart Citations